Analysis of trends in scientific publications by an NLP toolkit: A case study in Software Development Methods for Enhanced Living Environment - Girma, Melaku; Garcia, Nuno; Zdravevski, Eftim; Kifle, Mesfin; Pombo, Nuno; Trajkovikj, Vladimir (IEEE, 2020)
As the number of published scientific articles increases, the analysis of trends and state-of-the-art in software engineering is becoming very time-consuming and laborious task. To address the ever-growing demands for systematic literatures review techniques, rapid review and scoping reviews techniques have emerged. We used an NLP powered tool, which employs the PRISMA surveying methodology, to automate most of the review processes. We used it to automatically review relevant articles indexed in IEEE Xplore, PubMed and Springer digital libraries on the topic “Software Development for Enhanced Living Environments and Ambient Assisted Living”. The relevant articles identified by the NLP toolkit contained up to 21 properties clustered into 3 logical groups. We discovered that Software Development for Enhanced and Assisted living environments attracted an increased attention from the scientific communities over the last 10 years and showed several trends in the specific research topics that fall into this scope. The research uncovered that iterative software methodology had been the most attractive research topic in the field. Despite the enormous empirical evidence on application and success stories of agile development methodologies in many software development engineering, it received a little attention from the scientific community in the software development for Enhanced and Assisted Living Environments. The NLP toolkit identified the most relevant articles that contained the defined properties in the search. Hence, it significantly reduced the manual work, while also generating informative tables, charts and graphs.
Keywords: software development for enhanced living environments; Software development for ambient assisted living; NLP toolkit; Automated surveys; Scoping review;Systematic review;Rapid review